2013
DOI: 10.1158/0008-5472.can-12-4367
|View full text |Cite
|
Sign up to set email alerts
|

Integration of High-Resolution Methylome and Transcriptome Analyses to Dissect Epigenomic Changes in Childhood Acute Lymphoblastic Leukemia

Abstract: B-cell precursor acute lymphoblastic leukemia (pre-B ALL) is the most common pediatric cancer. Although the genetic determinants underlying disease onset remain unclear, epigenetic modifications including DNA methylation are suggested to contribute significantly to leukemogenesis. Using the Illumina 450K array, we assessed DNA methylation in matched tumor-normal samples of 46 childhood patients with pre-B ALL, extending single CpG-site resolution analysis of the pre-B ALL methylome beyond CpG-islands (CGI). Un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 53 publications
3
43
0
Order By: Relevance
“…Previous studies in ALL have identified inverse correlations between gene expression and DNA methylation in CGIs, CGI shores and gene promoters. 32 In this study, 99% of DMRs associated with a CGI were hypermethylated in ALL; however, these only accounted for a small number of the total DMRs. In fact, more than 80% of DMRs were identified in intronic or intergenic regions and not within a CGI context.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies in ALL have identified inverse correlations between gene expression and DNA methylation in CGIs, CGI shores and gene promoters. 32 In this study, 99% of DMRs associated with a CGI were hypermethylated in ALL; however, these only accounted for a small number of the total DMRs. In fact, more than 80% of DMRs were identified in intronic or intergenic regions and not within a CGI context.…”
Section: Discussionmentioning
confidence: 51%
“…We and others have reported previously that results from the HumanMethylation450 BeadChips (HM450) are technically robust but that there is a measurable false discovery rate [24, 25] . Thus, we initially conducted technical validation studies and biological validation studies of a subset of differentially methylated CpGs (N=4) found on the HM450 arrays (described in detail in Supplemental Methods and Results).…”
Section: Resultsmentioning
confidence: 99%
“…Maximal repression requires the binding of mSin3A, N-CoR and histone deacetylase-3 (HDAC3) to ETV6 [72]. Although the E/R chimeric protein is assumed to act as transcriptional repressor of RUNX1 target genes, several studies have reported similar levels of gene repression and activation for protein-coding and miRNA genes [68, 71, 75]. In addition, the E/R fusion gene product can disrupt the transcriptional repression of wild-type ETV6 by dimerization via the PNT domain [76].…”
Section: Pathogenesis Of Etv6/runx1-positive Childhood Allmentioning
confidence: 99%